Phaeosphaeriopsis omaniana (Phaeosphaeriaceae, Pleosporales), a novel fungus from Oman - Al-Jaradi, Asma J.; Maharachchikumbura, Sajeewa S. N.; Al-Sadi, Abdullah M. (Phytotaxa, 2020)
A fungus within the genus Phaeosphaeriaceae was isolated from brown leaf spot samples of Dracaena serrulata Baker (Yemen dragon tree) collected from Oman Botanic Garden, Muscat, Oman. Detailed morphological studies showed that this strain fits well within the species concept of the genus Phaeosphaeriopsis. Multilocus phylogeny based on LSU, ITS and TEF confirmed its uniqueness and supports its recognition as a new species, Phaeosphaeriopsis omaniana. Geography, pathogenic life mode and subglobose, smooth and brown conidia of the newly described species clearly differ from those of phylogenetically related species. A comprehensive description and illustrations of the new species, P. omaniana is provided and discussed with comparable taxa.